2007
DOI: 10.1080/17470210601119134
|View full text |Cite
|
Sign up to set email alerts
|

Two Modes of Sensorimotor Integration in Intention-Based and Stimulus-Based Actions

Abstract: Human actions may be driven endogenously (to produce desired environmental effects) or exogenously (to accommodate to environmental demands). There is a large body of evidence indicating that these two kinds of action are controlled by different neural substrates. However, only little is known about what happens--in functional terms--on these different "routes to action". Ideomotor approaches claim that actions are selected with respect to their perceptual consequences. We report experiments that support the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
237
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(269 citation statements)
references
References 38 publications
27
237
5
Order By: Relevance
“…This finding was also true for both forced-and free-choice tasks to the same degree (see also, e.g., Pfister & Kunde, 2013). This substantiates the increasing evidence that effect anticipation is a ubiquitous feature of both tasks, and is not restricted to free-choice tasks or intention-based action modes, as envisaged by, for example, Herwig et al (2007).…”
Section: Summary Of the Results And Relation To Other Studiessupporting
confidence: 81%
See 1 more Smart Citation
“…This finding was also true for both forced-and free-choice tasks to the same degree (see also, e.g., Pfister & Kunde, 2013). This substantiates the increasing evidence that effect anticipation is a ubiquitous feature of both tasks, and is not restricted to free-choice tasks or intention-based action modes, as envisaged by, for example, Herwig et al (2007).…”
Section: Summary Of the Results And Relation To Other Studiessupporting
confidence: 81%
“…In particular, it has been suggested that action effects and anticipatory mechanisms may not play a role at all in so-called forced-choice tasks-that is, tasks in which certain stimuli determine the one and only correct response (e.g., Herwig, Prinz, & Waszak, 2007). In contrast, a free-choice task-that is, one in which a certain stimulus asks the participant to choose between two equally appropriate responses (Berlyne, 1957)-induces an "intention-based action control mode" wherein effect anticipations do play a role.…”
Section: Ideomotor Theory and Effect-based Action Controlmentioning
confidence: 99%
“…This feedback serves two purposes. First, movement features in long-term memory may be activated via the representation of the intended sensory feedback (Herwig, Prinz, & Waszak, 2007;Hommel, Müsseler, Aschersleben, & Prinz, 2001). Second, the expected feedback allows ongoing movements to be monitored for errors and, in the case of relatively slow movements, to correct these movements (Adams, 1971).…”
Section: Assumption 1: Representationsmentioning
confidence: 99%
“…If participants prepare to respond to a stimulus (i.e., in the so-called stimulus-based or externally guided mode; Herwig et al, 2007;Tubau et al, 2007) they actually pass on control to the display of a limited set of stimuli. Setting this external control mode involves the advance loading of a stimulus set and of stimulus-response translation rules into short-term memory.…”
Section: Assumption 6: Cognitive Controlmentioning
confidence: 99%
“…Changes in postural orientation can produce a change in perception of the environment [20]. These behaviors are also modulated by both intention-based and stimulus-based actions (feedforward and feedback) [9] indicative of ascending as well as descending control processes. The presence of redundant control mechanisms permits a successful outcome with response variability and task dependence.…”
Section: Introductionmentioning
confidence: 99%